2016
DOI: 10.1007/s00264-015-3103-1
|View full text |Cite
|
Sign up to set email alerts
|

Peri-operative blood-loss after total hip arthroplasty can be significantly reduced with topical application of epsilon-aminocaproic acid

Abstract: This study demonstrates a significant reduction in peri-operative blood loss after THA with topically applied ε-ACA. The application of ε-ACA reduced costs by lowering transfusion rates and did not increase thrombo-embolic events. ε-ACA is safe and effective in reducing blood loss and cost-efficient in THA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
0
10
1
Order By: Relevance
“…It consists of two steps: degradation of fibrin and activation of plasminogen [23]. Antifibrinolytic agents such as TXA and EACA decrease blood loss by attenuating this fibrinolytic process [68].…”
Section: Discussionmentioning
confidence: 99%
“…It consists of two steps: degradation of fibrin and activation of plasminogen [23]. Antifibrinolytic agents such as TXA and EACA decrease blood loss by attenuating this fibrinolytic process [68].…”
Section: Discussionmentioning
confidence: 99%
“…Five articles [18–22] showed the total blood loss after TJA. A random-effect model was adopted (χ 2 = 0.78, df = 4, I 2 = 0%, P = .941).…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
“…Three articles [19,21,22] reported postoperative drain output. There was significant difference in terms of postoperative drain output between groups (SMD = −2.162, 95% CI: −2.678 to −1.646, P <.001; Fig.…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
“…[ 10 , 11 ] Guerreiro et al [ 12 ] reported intravenous tranexamic acid reduced intraoperative and postoperative blood loss and thus reduced the need of allogenic blood transfusion in total knee arthroplasty. Sucher et al [ 13 ] indicated that intraoperative use of aminocaproic acid did not appear to increase the risk of postoperative complication in total hip arthroplasty. Compared with total joint arthroplasties, PAO was associated with more blood loss and higher transfusion rates.…”
Section: Introductionmentioning
confidence: 99%